Analisis Hukum Islam Dan Hukum Positif Nafkah Madiyyah Terhadap Putusan Nomor 328/Pdt.G/2018/PA.Gsg - Violensy, Cahyaning; Nurnazli, Nurnazli; Santoso, Rudi; Zaharah, Rita; Ramlan, Ramlan (UIN Fatmawati Sukarno Bengkulu, 2025)
Among the obligations that must be fulfilled by a father or husband within the family structure is providing maintenance for those under his responsibility, including his wife and children. Both Islamic law and positive law firmly regulate the provision of maintenance. Furthermore, failure or deliberate neglect by a father to provide maintenance may be legally pursued through the religious courts. This article analyzes Islamic Law and Positive Law regarding nafkah mahdiyah (post-divorce maintenance) in Decision Number 328/Pdt.G/2018/Pa.Gsg, with the aim of examining how the judge’s decision reflects justice based on Islamic law and positive law. This study employs a documentation research method, supported by library research facilities. The approach used is a normative juridical approach, aiming to synchronize the existing legal provisions in the protection of legal norms and other regulations. The findings show that, in deciding nafkah mahdiyah cases, Indonesian judges harmonize Islamic law and positive law. According to Islamic law, a husband is obligated to provide maintenance to his wife during the iddah period. In positive law, this obligation is regulated under Article 156 letter (d) of the Compilation of Islamic Law (KHI), which mandates former husbands to provide maintenance. Judges consider the husband's financial ability and the evidence presented in court, referring to both Sharia norms and positive legal provisions to render a fair and proportional decision.